Nothnagel Syndrome: A rare case of Ischemic Brain Stem Syndrome (Journal of Medicine, 2019)
‘Nothnagel Syndrome' is a brainstem syndrome which is often underdiagnosed by the physicians due to rarity of the disease and complex clinical presentation. We present a case of brainstem midbrain syndrome caused by ischemic stroke. The male hypertensive diabetic patient presented with sudden onset of diplopia, ptosis and gait imbalance. Right-sidedgaze palsy with nystagmus and ataxic gait were the clinical findings. Brain imaging (MRI and DWI) showed high signal intensity at upper midbrain. The patient was finally diagnosed as ischemic stroke in the brainstem called Nothnagel syndrome. Up to now, there was no case reported as Nothnagel Syndrome due to ischemic stroke.J MEDICINE JAN 2020; 21 (1) : 62-64